Cohort Removal Induces Changes in Body Temperature, Pain Sensitivity, and Anxiety-Like Behavior - Takao, Keizo; Shoji, Hirotaka; Hattori, Satoko; Miyakawa, Tsuyoshi (Frontiers in Behavioral Neuroscience, 2016)
Mouse behavior is analyzed to elucidate the effects of various experimental manipulations, including gene mutation and drug administration. When the effect of a factor of interest is assessed, other factors, such as age, sex, temperature, apparatus, and housing, are controlled in experiments by matching, counterbalancing, and/or randomizing. One such factor that has not attracted much attention is the effect of sequential removal of animals from a common cage (cohort removal). Here we evaluated the effects of cohort removal on rectal temperature, pain sensitivity, and anxiety-like behavior by analyzing the combined data of a large number of C57BL/6J mice that we collected using a comprehensive behavioral test battery. Rectal temperature increased in a stepwise manner according to the position of sequential removal from the cage, consistent with previous reports. In the hot plate test, the mice that were removed first from the cage had a significantly longer latency to show the first paw response than the mice removed later. In the elevated plus maze, the mice removed first spent significantly less time on the open arms compared to the mice removed later. The results of the present study demonstrated that cohort removal induces changes in body temperature, pain sensitivity, and anxiety-like behavior in mice. Cohort removal also increased the plasma corticosterone concentration in mice. Thus, the ordinal position in the sequence of removal from the cage should be carefully counterbalanced between groups when the effect of experimental manipulations, including gene manipulation and drug administration, are examined using behavioral tests.